"USIDLENIE W DZIECIŃSTWIE” ‒ DOŚWIADCZANIE NIEZASPOKOJENIA EMOCJONALNEGO W RODZINIE. UJĘCIE SOCJOLOGICZNE - Szluz, Beata (TNFS, 2020)
Parents who are emotionally unavailable are often immature and psychologically affected themselves. As difficult as it is to believe, emotionally distant parents face their own emotional problems that might go back as far as to their own childhood and be rooted in the attitude of their own parents often unable to meet the emotional and psychological needs of their child. Typical symptoms characteristic of adults who are emotionally immature and detached include, but are not limited to: rigidity, low stress tolerance, emotional instability with aggression, unstable relationships and attention-seeking. The paper aims to present difficulties encountered by people experiencing emotional dissatisfaction in the family (in sociological terms).

Rodzice, którzy są niedostępni emocjonalnie, często sami są emocjonalnie niedojrzali. Mają wiele własnych problemów, które sięgają okresu ich dzieciństwa. Występował w ich życiu deficyt rodziców, którzy nie byli w stanie zaspokoić emocjonalnych i psychologicznych potrzeb swojego dziecka. Objawy występujące u osób dorosłych, niedojrzałych emocjonalnie obejmują między innymi: sztywność emocjonalną, niską tolerancję na stres, niestabilność emocjonalną z agresją, niestabilne relacje oraz szukanie uwagi. W artykule podjęto próbę ukazania problemów, z którymi spotykają się osoby doświadczające niezaspokojenia emocjonalnego w rodzinie (w ujęciu socjologicznym).
“ENTANGLEMENT IN CHILDHOOD” ‒ EXPERIENCING EMOTIONAL NEGLECT IN THE FAMILY. SOCIOLOGICAL APPROACH
-
Keywords: sociology of family; socjologia rodziny; sociology of social problems; emotional neglect syndrome; family; biographical method; socjologia problemów społecznych; zespół niezaspokojenia emocjonalnego; rodzina; metoda biograficzna